PENGARUH KULITAS DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK WARDAH, MAKEOVER DAN EMINA - Safira, Anggita Maudilla; Prabowo, Prayudi Setiawan (Jurnal Ekonomika dan Bisnis Islam, 2020)
The development of the cosmetics industry in Indonesia in 2010 - 2015 has increased every year. This is evidenced by the high level of cosmetics production in Indonesia. With that, the cosmetics industry is given the trust to produce good quality cosmetic products. This study aims to determine the effect of product quality (X1) and promotion (X2) on purchasing decisions (Y) of Wardah, MakeOver and Emina cosmetic products. The sample used in this study were 100 Muslim female respondents who used Wardah, MakeOver and Emina cosmetics in Surabaya. The approach taken in this research was an associative quantitative approach. Primary data obtained from the distribution of questionnaires to consumers who use Wardah, MakeOver and Emina cosmetics. The analysis technique used in this research was Partial Least Square (PLS) analysis. The results of this study indicated that product quality has a positive and significant effect on purchasing decisions. In addition, promotion also affected positively and significantly on purchasing decisions.